"Composing with Tones" A Musical Analysis of Schoenber's Op. 23 Pieces for Piano - Simms, Bryan R. (Oxford University Press, Oxford, 2003)
RESUMEN: Autora Kathryn Bailey. Royal Musical Association Monographs, 10. Royal Musical Association, London, 2001.